PENERAPAN KURIKULUM BERBASIS KOMPETENSI DI PESANTREN DALAM MENCIPTAKAN SANTRI UNGGUL DAN MANDIRI - Noer Rohmah; Roihanah (Jurnal Studi Pesantren, 2022)
One of the curriculum development processes in Islamic boarding schools is directed at the formation of students who have superior and independent characters as indicators, among others, are obedient to worship, have noble character, have integrity, are able to work well together, do not depend on others and so on. One way to make it happen is to implement a competency-based curriculum, namely a curriculum that emphasizes the emergence of "ability" namely the ability to live life through the application and development of knowledge, skills and attitudes. So that the pesantren is able to produce students who are not only experts in the field of religion but also have other skills while still having superior character and being able to be independent. If thousands of students who have been scattered throughout the Indonesian archipelago have been educated to be independent, an independent society will be realized and thus will greatly support the establishment of an independent nation.